Densitas Bakteri pada Limbah Cair Pasar Tradisional - . Lizayana; . Mudatsir; . Iswadi (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2016)
One of the places most visited by people every day is a traditional market. Various activities such as buying and selling various household purposes can be found the place. The activity becomes one cause of waste that must be overcome market. The waste produced can be either solid waste and wastewater management. Liquid wastes big opportunities for development of various microorganisms that are harmful to humans, such as the bacterium Escherichia coli and the like. Traditional markets liquid waste generated every day cause various health problems such as diarrhea and the others. The disorder is caused by bacterial pathogens present in the liquid waste. Research Density Bacteria are the Liquid Waste Traditional Market has been held on since February-March 2016. This study aims to determine the density of the bacteria present in the wastewater traditional markets in the city of Banda Aceh. The sample in this study is the liquid waste sanitation traditional markets, namely the Rukoh Market, Peunayong Market, Neusu Market, Keutapang Market, and Seutui Market. The method used in this research is descriptive. Data collection was carried out in three stages, namely liquid waste sampling, measurement of the value of Optical Density (OD), and Total Plate Count (TPC). The results obtained by bacterial density is highest in the wastewater by the number of colonies as much as 20 x 1010 CFU / ml at 10-9 dilution level that has a value Optical Density (OD) is the highest in the market Seutui 0512 nm, while the fewest number of bacterial colonies found in wastewater with the number of colonies of bacteria 3 x 107 CFU / ml at the rate of dilution of 10-6 which has the lowest value of optical density is 0.051 nm at Rukoh Market.